Watch out for malaria: still a leading cause of child death worldwide - Buonsenso Danilo; Cataldi Luigi (BMC, 2010)
Abstract Background Due to the efforts in malaria control promoted by the World Health Organization (WHO), the reported malaria burden is being reduced throughout the world. Nevertheless, malaria remains a leading cause of child death worldwide. Aims purpose of the paper is to summarize the main historical steps in fighting malaria, from the first descriptions to the last ones. Results a case of probable autochthonous malaria has been recently described in Italy, raising concern over the possibility of resurgence of malaria in countries previously interested by this disease. Moreover, both the constant threat of the parasite and vector mosquito developing resistance to medicines and insecticides, and the on-going climate change make the challenge of eradicating malaria really difficult. Therefore, malaria is still an actual disease, requiring adequate programs of surveillance, stronger health systems in poor countries, and efforts in order to develop new and effective tools in malaria control. WHO has definitely demonstrated the effects of "social determinants" on health. So, eradication strategies cannot be based only on a scientific background, because culture, politics, power, resources and wars have a profound impact on health and disease. These elements should be introduced in all the programs of malaria control. Conclusions malaria is still an actual disease with great public health implications, and the approaches for control and prevention should have the appropriate social and political context in addition to the science involved in order to save lives of children at risk.